Still Mad–On Feminism, Anger, and the Current State of U.S. Women’s Rights - Höpker, Karin (New American Studies Journal: A Forum, 2022)
The current state of Women’s Rights in the United States is a matter of grave concern and thus, without question, a core topic for an issue on “American Crises.” An altered Supreme Court and individual state legislation like the 2021 Texas Heartbeat Act raise distinct concerns over human rights issues, women’s reproductive rights, and the potential dismantling of Roe v Wade. The Trump administration and the January 6 insurrection gave new urgency to debates over toxic masculinity and its relation to populism and the media. The frustration over gender inequality, care work gaps, and the toll of emotional labor has been exacerbated by the pandemic. Recent Supreme Court nomination hearings have also raised new concerns about gender equity.<br